Characterization of Silica from Pasir Puteh, Kelantan Rice Husk for Water Filter Application - Bin Abd Aziz, Amirul Eizlan Hadi; Ahmad, Sufizar (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Water is a basic need for every human being but in order to get clean and safe water, water needs to be treated and filtered so that the water is safe for humans to drink and use. Therefore, the initiative to help this problem is to produce a ceramic type water filter from rice husk. Rice husk is an agro waste that is very much produced in this world. By applying rice husk, the problem of large piles of rice husks can be reduced. In this study, water filter samples were produced from burned rice husk (BRH). The filter composition is 95% BRH and 5% Polyethylene Glycol (PEG). Water filter samples were produced using powder compaction method. Then, the filter go through the sintering process at a temperature of 900 °C, 1000°C and 1100°C. Density and porosity tests as well as water absorption tests were performed to see the physical properties of the water filter samples. The analysis performed is microstructural analysis and element composition analysis. Sample C showed the highest bulk density with value of 1.3153 g/cm3 and the lowest apparent porosity percentage with value of 39.89%. The percentage of water absorption in sample C was the lowest at 30.35%. Therefore, the best water filter sample is sample C based on the test results. In conclusion, the sintering temperature affects the physical properties of the water filter samples produced from the BRH.